Aerobic Exercise Training as a Potential Cardioprotective Strategy to Attenuate Doxorubicin-Induced Cardiotoxicity - Kouzi, Samir A.; Uddin, Mohammad Nasir (Journal of Pharmacy & Pharmaceutical Sciences, 2016)
Doxorubicin is one of the most commonly used cytotoxic anticancer drugs against several cancers. Although a highly effective anticancer drug, the clinical use of doxorubicin is severely limited by its cardiotoxicity which results in morbidity, poor quality of life, and premature mortality. Only very few clinically accepted methods to minimize doxorubicin-induced cardiac injury are available today, but none of them have proven to be completely successful. Due to limited alternative strategies, a number of potential cardioprotective therapies are currently being investigated for treating and/or preventing doxorubicin-induced cardiotoxicity. Of these potential strategies, aerobic exercise training is the only nonpharmacologic strategy that shows a great deal of promise. Although there are no published human clinical trials, evidence from numerous animal studies suggests that aerobic exercise training, administered prior to, during and/or following doxorubicin therapy, is protective against doxorubicin-induced cardiac injury. Protective properties of exercise training against the cardiotoxicity of doxorubicin have been attributed to a number of potential molecular mechanisms including: enhancing the production of endogenous antioxidant machineries; regulating proapoptotic signaling; stimulating the release, mobilization and homing of cardiac progenitor cells; limiting myocyte turnover; eliciting favorable adaptations in myocardial calcium handling and preventing calcium overload; modulating cardiac AMPK activity; downregulating cardiac autophagy/lysosomal signaling; and reducing myocardial doxorubicin accumulation. Further preclinical and clinical research is needed to decipher and refine the molecular mechanisms underlying the cardioprotective effects of exercise training, as well as to define the nature and magnitude of the effect of exercise on doxorubicin-induced cardiotoxicity in cancer patients. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.